Economic Burden Conferred by Population-Level Cancer Screening on Resource-Limited Communities: Lessons From the ESECC Trial - Li, Fuxiao; Hu, Yanjun; Guo, Chuanhai; Lei, Liang; Li, Fenglei; Liu, Mengfei; Liu, Zhen; Pan, Yaqi; Liu, Fangfang; Liu, Ying; Hu, Zhe; Chen, Huanyu; et al. (Frontiers in Oncology, 2022)
Abstract Objectives Upper gastrointestinal (G.I.) cancer screening has been conducted in China for decades. However, the economic burden for treatment “intensively” occurred in advance due to screening in resource-limited communities remain unclear. Methods We compared the treatment costs for upper G.I. cancers from the screening and control arms of a population-based randomized trial in a high-risk area for esophageal cancer (EC) in China based on the claims data from the health insurance system with whole population coverage in the local area. Results The average out-of-pocket cost per treatment of EC in the screening arm was lower than that in the control arm ($5,972 vs. $7,557) due to down-staging by screening and less-costly therapy for earlier stages, and the result is similar for cardial and non-cardial gastric cancer in the two arms ($7,933 vs. $10,605). However, three fold (103 vs. 36) families in the screening arm suffered from catastrophic health expenditure for all cancer types. The overall treatment cost for all EC patients in the screening arm ($1,045,119) was 2.44 times that in the control arm ($428,292), and the ratio for cardial and non-cardial gastric cancer was 1.12 ($393,261 vs. $351,557). Conclusion Cancer treatment secondary to screening may triple the occurrence of catastrophic medical expenditure among patients, and sharply increase the economic pressure on the local community, particularly for the high prevalent cancer types. Financial support for patients and the health insurance system should be considered when planning budgets for cancer screening programs in resource-limited communities.